Development and Application of an Integrated Monitoring and Early Warning Platform for Land Transportation Infrastructure under Special Engineering Conditions. (7th June 2022) - Zhang, Liujun; Qiu, Youqiang; Yu, Hui; Yin, Lihua; Zhang, Faru; Wu, Tong
Abstract : To ensure the safety service performance of land transportation infrastructure under special engineering conditions, centering on the characteristics of structures such as the road high-steep slope, high embankment, special subgrade, railway track, and airport pavement, an integrated monitoring and early warning platform based on health monitoring and safety evaluation was built through the combined design of the safety indicator module, monitoring data module, information processing module, numerical simulation module, inversion prediction analysis module, and safety early warning module. The data interaction between the integrated platform and five monitoring subplatforms was realized by the B/S mode, and the related function interfaces were established. The research results show that as the monitoring data storage analysis and early warning carrier, the integrated monitoring and early warning platform not only presents key data such as comprehensive early warning information, evaluation indicators, and monitoring elements but also realizes the intelligent, automatic, and visual presentation of monitoring data. In addition, relying on the high-steep slope of the Hohhot-Bikeqi Highway (section: K528+215 K528+525), through the application of the high-steep slope monitoring and early warning subplatform system in the practical project, it is verified that the platform has a good monitoring and early warning effect, which provides a reliable platform guarantee for the health monitoring and safety operation of the project.